PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 015 BANJAR XII KABUPATEN ROKAN HILIR - Rimawati Rimawati; Hendri Mahardi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem in this research was conducted because of the low of IPS learning result of fourth grader of SD Negeri 015 Banjar XII, with the average of 58,8 class. The formulation of the problem "Is the application of Problem Based Learning (PBL) can improve the learning outcomes of IPS fourth graders Elementary School 015 Banjar XII Tanah Putih District?". This study aims to improve the learning outcomes of IPS fourth grade students of Elementary School 015 Banjar XII Tanah Putih sub-district by applying the model of Problem Based Learning (PBL). This research is a classroom action research that uses several stages of action implementation consisting of two cycles. In this study each cycle consists of 3x meetings consisting of 2 (two) times the material and 1 (one) time Final Exam. The problem studied in this research is the problem of learning. Each cycle in this research is carried out in four stages: (1) planning, (2) implementation, (3) Observation, (4) Reflection. This research was conducted on March 14, 2017 until April 19, 2017. The subjects of this study are the fourth grade students of SD Negeri 015 Banjar XII with 25 students, 9 male students and 16 female students. The instrument of data collection in this thesis is observation sheet of teacher and student activity and learning result based on Daily Deuteronomy. The result of research of teacher activity in learning process at first cycle of first meeting was got the average value of 65% and the second meeting increased to 75.00%. In the second cycle of the first meeting 85.00% and the second meeting increased to 90.00%. Results of data analysis of student activity on first cycle of first meeting 60.00% and second meeting increased to 70.00%. In the second cycle of the first meeting 75.00% and the second meeting increased to 80.00%. Based on the results of data analysis, the average learning outcomes before the action is an average of 58.8 (less categories). After the action increases in cycle I with average to 67.2 (enough category). In the second cycle increased by an average of 77 (good category). Means that the implementation of Problem Based Learning (PBL)can improve the learning outcomes of IPS fourth graders Elementary School 015 Banjar XII Tanah Putih subdistrict.Keywords: Problem Based Learning, IPS Learning Outcomes